Patient Reported Experience Measures in navigated Transcranial Magnetic Stimulation. (12th October 2019) - Patel, Sabina; Lavrador, José; Ghimire, Prajwal; Gullan, Richard; Ashkan, Keyoumars; Bhangoo, Ranjeev; Vergani, Francesco
Abstract: Introduction: Navigated Transcranial Magnetic Stimulation (nTMS) is a non-invasive adjunct used in surgical planning for lesions in eloquent brain. However, its patient tolerability and effect on their overall healthcare experience is still unknown. To our knowledge, there is no other literature available evaluating patient experience with nTMS. Methods: A single-institution prospective cohort study carried out between February 2018 and December 2018 at King's College Hospital. All patients were supplied with a PREMs-TMS questionnaire to evaluate the different domains of the nTMS experience. Results: Feedback was obtained from 50 patients. 26% of patients underwent motor mapping (MM), whilst 74% underwent both motor and language mapping (MLM). The former group reported a better overall experience (p=0.020). The mean exam duration was 103.3±5.1 min (MM 85.8±6.1 min; MLM 106.9±5.9 min). The whole experience of nTMS received positive feedback (94%), particularly with confidence in the staff (95%). Unsurprisingly, the exam domain received a poorer rating (70% as good) with significant anxiety and pain reported in 26% and 24% of patients respectively. None of the studied variables influenced the way patients rated the overall experience of nTMS (p>0.05). Conclusions: nTMS is a non-invasive investigative tool, which allows patients to better understand their condition and symptoms related to their lesion. Serial assessment and feedback using a PREM tool, can only improve and enhance this experience. Departmental collaboration may be useful in comparing patient experience with nTMS in different centres.